PENGARUH KEPATUHAN DAN PENGETAHUAN RAMBU KESELAMATAN TERHADAP KESELAMATAN KERJA DI LABORATORIUM PT GEOSERVICES BALIKPAPAN - Hardiyono, Hardiyono (IDENTIFIKASI, 2019)
Analysis of the level of compliance and knowledge of employees with the protection of safety signs, whether it affects the level of awareness of workers on the danger of working safety at PT Geoservices Balikpapan. The method used in this study is a method with a quantitative approach through questionnaires and then in view of a qualitative approach through observation and interviews aiming to get a full picture of the influence Compliance and knowledge of occupational safety. There is a result of a double linear association which is: Y = 2,782 +1, 000X1 +1, 000X2 which if the relationship of constant coefficient a = 2,782 indicate that if compliance and knowledge remain/do not experience addition or subtraction, then occupational and safety constant value of 2.782. Each increment of one unit of safety signs compliance then occupational safety will increase by 1,000. Each increase in knowledge of safety signs of one unit and then safety will increase by 1,000. In addition, there is a percentage result of the tested coefficient of determination which is used to determine how large the percentage of contributions of independent variable influence simultaneously on its dependencies variable. This is shown with the result of a coefficient of determination in the level of knowledge on occupational safety shows the value of 0,643 so that the contribution of the knowledge independent variable of 64,3% to the dependent variable of occupational safety While the rest is 35,7% in influence other factors.